The Oblivion of Holocaust as Historical Process: The Case of Vabalninkas’ Dwellers - Sederevičiūtė, Šarūnė (Lietuvos istorijos studijos, 2016)
This article presents a micro-history research based on the collective memory of North Lithuania’s township Vabalninkas. The main target was the Catholic Lithuanians’ memory concerning the profuse Jewish community which used to live in the town. This memory formed from around 1930’s to current day (2015). Based on the conducted research the aim is to reveal a process which formed a current amnesiac situation of memory and explain it.First, the effect of Holocaust on the Lithuanian part of Vabalninkas community was analysed through interviews with witnesses. Second, the conditions of the Soviet period were reconstructed, which shaped particular discourse of memory. Finally, some attempts to arouse the memory about Jews after Lithuania’s independence as well as current situation are presented. The questions of the research were as follows: could we say that there is a collective memory concerning Jews in Vabalninkas today? What are the main features of the memories about Vabalninkas Jews? In which layers of memory (individual, collective, public) Vabalninkas’ Jews appear? Why? What historical circumstances could have determined the current condition of township’s community memory?The case of Vabalninkas showed that an ambiguous historical, cultural, social and psychological process lurks under the local community’s collective Jewish amnesia: first – sociocultural trauma (dramatic and unexplainable fracture in everyday experience); second – fundamental demographic changes during Soviet times caused by war losses as well as voluntary and forced migration. Tangled together they created a situation where marginal individual memory about Jews does not find any place in the collective memory of the newer generations of Vabalninkas people since it is alien to the majority of population’s identities. However, it still exists in spatial signs and older population’s feelings of alienation further creating unarticulated tension expressed by unconscious avoidance of Jewish topic. It is important to note that in individual perspectives of Holocaust contemporaries it is hard to grasp any signs of guilt or responsibility which are prominent in present public discussions about Lithuanians’ role in the Holocaust. The majority of population during Nazi occupation were only passive observers so the traumatic memory should first be attributed to social and cultural break which left people with an unanswered question why and made them unable to insert this extraordinary experience into social frames.Following this approach some untouched issues emerge in the Holocaust studies which could, for example, focus on the strategies of coping with this trauma. One of these strategies, unconscious oblivion, was revealed by researching the memory of Vabalninkas.
Keywords: memory; jews; Holocaust; Vabalninkas